Pengaruh Arus Kas terhadap Kinerja Keuangan Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Shahlaila Lutfia Rahman; Isni Andriana; Kemas M. Husni Thamrin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze cash flows that can influence net profit, using the variables Funding Cash Flow, Investment Cash Flow and Operation Cash Flow in Mining sector companies listed on the Indonesia Stock Exchange. This research was taken from the last five years, namely 2018 to 2022. The sampling technique used purposive sampling to obtain 55 companies. The type and source of data used is secondary data in the form of published financial reports. The data analysis technique used in this research is multiple linear regression analysis with SPSS software. The results of this research show that Funding Cash Flow and Investment Cash Flow have a significant effect on Net Profit. Meanwhile, Operating Cash Flow does not have a significant effect on Net Profit in Mining sector companies listed on the Indonesia Stock Exchange from 2018 to 2022